Global Dynamics of the Cahn-Hilliard/Allen-Cahn Equation (Journal of Mathematical Study, 2023)
In this paper, we consider the global dynamics of the Cahn-Hilliard/Allen-Cahn equation with periodic boundary value conditions in 2D bounded domain $Ω.$ We show that the equation has a global attractor in $H^4_{per}(Ω)$ when the initial valuebelongs to $H^1_{per}(Ω).$